Impact of Henda's law on the utilization of screening breast magnetic resonance imaging - Mason, Callan (Proc (Bayl Univ Med Cent), 2015)
Female breast tissue is composed of variable proportions of fat and fibroglandular tissue, and in general, an increased ratio of fibroglandular tissue to fat corresponds to increased mammographic density. Studies suggest that mammographic density is an independent risk factor for breast cancer, and the sensitivity of mammography can be lower with heterogeneously dense or extremely dense breasts. Nineteen states have legal statutes requiring that patients be notified if they have dense breasts, including the state of Texas. Henda's law, mandated on January 1, 2012 in Texas, suggests that patients with dense breasts could benefit from additional screening tests such as breast magnetic resonance imaging (MRI). Our study examined the impact of Henda's law by comparing the number of screening breast MRIs performed for dense breasts before and after the law's implementation. Results showed a 23-fold increase in the number of dense breast MRIs in the 2 years that this new legislation was in effect. This increase could have substantial implications for the health care economy, and further studies are needed to determine the cost-effectiveness of this additional screening tool.